Marketing Strategy Implementation and Marketing Cases - Kahfi, Fahrul (Scieclouds Publishing, 2023)
This article discusses the implementation of marketing strategies and cases in marketing. The purpose of this article is to determine the implementation of a conceptual strategy formulation that must be realized in action-oriented company operations and the role of organization in the success of strategies related to the issue of synergy in strategy implementation. This article is also useful for knowing the monitoring and evaluation of strategies in the company and knowing the processes and characteristics of an effective evaluation in the supervisory process.